2016
DOI: 10.1007/s11858-016-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Assistance of students with mathematical learning difficulties: how can research support practice?

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 74 publications
2
49
0
5
Order By: Relevance
“…This observation should be an important prerequisite for apprising the educational usefulness of the proposed tool in a teaching practice. Nevertheless, our view (that is also supported by other recent study (Scherer et al , )) is that multimodal resources enhance children’s perception and facilitate the grasp of specific geometric relations. Currently, we plan to develop more user friendly versions of the applications in cooperation with a software company that will take into account users’ feedback.…”
Section: Discussionsupporting
confidence: 88%
“…This observation should be an important prerequisite for apprising the educational usefulness of the proposed tool in a teaching practice. Nevertheless, our view (that is also supported by other recent study (Scherer et al , )) is that multimodal resources enhance children’s perception and facilitate the grasp of specific geometric relations. Currently, we plan to develop more user friendly versions of the applications in cooperation with a software company that will take into account users’ feedback.…”
Section: Discussionsupporting
confidence: 88%
“…Various gaps such as these exist today; for instance, both gender differences and an achievement gap between majority and minority students are frequently visible in mathematics assessments (e.g., OECD 2013a(e.g., OECD , 2015Klenowski 2009). Indeed, we could point to several cases of inequitable assessment practices, for example with regard to centralised versus decentralised national examinations (Wößmann 2005) or assessments of students with special needs (Scherer et al 2016). In this review paper we use gender differences and the achievement gap between majority and minority students to illustrate how equity issues are linked to methodology and policy.…”
Section: Equity Issuesmentioning
confidence: 99%
“…This view contrasts with many intervention approaches that consider mathematics learning difficulties from a medical or psychological paradigm rather than as a social construct. Magne (2003) extensive review of the literature on special educational needs in mathematics found that a medical model was adopted in the majority of studies surveyed; this positions mathematics difficulties as innate deficiencies as opposed to a socially, culturally, and politically constructed facet of identity and experience (Scherer et al 2016). In the EMU approach, teachers focus on designing rich learning environments for all students that are responsive to differences in how children learn.…”
Section: The Extending Mathematical Understanding (Emu) Intervention mentioning
confidence: 99%
“…It commissioned a survey team to examine the state of the art with respect to the Assistance of students with mathematical learning difficulties-How can research support practice? (Scherer et al 2016). The survey results highlight shifting paradigms in understanding mathematics learning difficulties, and found that approaches for identifying and assisting children are moving away from medical models towards more inclusive approaches.…”
Section: Introductionmentioning
confidence: 96%